Consistency over three Olympic Games: A case study on Simon Withlfield - Filliol, J, (Science + Triathlon 2015 World Conference, 2015)
Canadian Simon Whitfield had an extra-ordinary career, spanning four Olympiads from Sydney 2000 where he was triathlon`s inaugural Gold Medalist, to 11th in Athens and then back to the podium with the Silver medal in Beijing 2008, and finally to London 2012.